2007
DOI: 10.1038/sj.ejcn.1602749
|View full text |Cite|
|
Sign up to set email alerts
|

Methodology for studying postprandial lipid metabolism

Abstract: Background: Postprandial lipid metabolism in humans has deserved much attention during the last two decades. Although fasting lipid and lipoprotein parameters reflect body homeostasis to some extent, the transient lipid and lipoprotein accumulation that occurs in the circulation after a fat-containing meal highlights the individual capacity to handle an acute fat input. An exacerbated postprandial accumulation of triglyceride-rich lipoproteins in the circulation has been associated with an increased cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
132
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 112 publications
(220 reference statements)
7
132
0
3
Order By: Relevance
“…The fat content of the loaded cream was about 35% of the fat ingested by an average Japanese adult woman in a day 26) . Although the vast majority of fat tolerance studies have employed 1-1.5 g fat/kg body weight 27) , such high amounts of fat limit the applicability of the results to everyday conditions for Japanese people; therefore, we utilized a fat cream (OFTT cream) with this moderate fat content 5,6) . VLDL and CM remnants (CMR) are similar in size and composition, and separation of the lipoprotein classes cannot be achieved by conventional methods such as ultracentrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…The fat content of the loaded cream was about 35% of the fat ingested by an average Japanese adult woman in a day 26) . Although the vast majority of fat tolerance studies have employed 1-1.5 g fat/kg body weight 27) , such high amounts of fat limit the applicability of the results to everyday conditions for Japanese people; therefore, we utilized a fat cream (OFTT cream) with this moderate fat content 5,6) . VLDL and CM remnants (CMR) are similar in size and composition, and separation of the lipoprotein classes cannot be achieved by conventional methods such as ultracentrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…First, a single evaluation of postprandial TG levels 2 hours after lunch could be inappropriate to capture the maximal TG concentration after the meal. Previous studies using a smaller fat load (~30 g) demonstrated peak plasma TG 4 hours after ingestion 39,40) . In the cohort study of Bansal et al, postprandial TG levels measured 2 − 4 hours after the last meal had the strongest association with future cardiovascular events 1) .…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of TAG-rich lipoproteins (TRLs; chylomicrons and very low density lipoprotein) in both the fed (postprandial) and fasted states is the metabolic driver of a combined dyslipidaemia referred to as the atherogenic lipoprotein phenotype, and a clinical feature of type 2 diabetes and the metabolic syndrome. The atherogenic impact of TAG is thought to be mediated in part by a reduction in high density lipoprotein cholesterol (HDL-C) concentration and a decrease in the size of low density lipoprotein (LDL) towards the smaller more atherogenic LDL-III and LDL-IV particles [23]. Importantly, the dyslipidaemia is highly correlated with excess body weight and because of the increasing prevalence of both overweight and obesity, its occurrence in the UK, especially in middle-aged men and women, is extremely common [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since Zilversmit [42] hypothesised that TRL remnants were atherogenic in 1979, there has been considerable research interest into the acute and chronic impact of dietary fat composition on postprandial lipaemia. However, determination of the postprandial response is complex and the lack of standardisation of methodologies, in particular test meal size and composition, between different studies and research groups has hampered the elucidation of lifestyle and physiological factors which influence postprandial lipaemia [23]. In addition, the degree of certainty that can be placed on summary measures of the lipaemic response is often limited by small subject numbers and infrequent blood sampling during the postprandial period.…”
Section: Introductionmentioning
confidence: 99%